8p+8q=8(p+q)

Simple and best practice solution for 8p+8q=8(p+q) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8p+8q=8(p+q) equation:


Simplifying
8p + 8q = 8(p + q)
8p + 8q = (p * 8 + q * 8)
8p + 8q = (8p + 8q)

Add '-8p' to each side of the equation.
8p + -8p + 8q = 8p + -8p + 8q

Combine like terms: 8p + -8p = 0
0 + 8q = 8p + -8p + 8q
8q = 8p + -8p + 8q

Combine like terms: 8p + -8p = 0
8q = 0 + 8q
8q = 8q

Add '-8q' to each side of the equation.
8q + -8q = 8q + -8q

Combine like terms: 8q + -8q = 0
0 = 8q + -8q

Combine like terms: 8q + -8q = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 3xy(5x-3)= | | 12x/78x | | 2x-(4+x)=7 | | 2x+x+6x=153 | | 5-3x+2=8-3x | | 2x-4*(x-4)=2y | | 9m*(-3)= | | x^3-45x^2+10000=0 | | 4x+3-x=-6x-7 | | 7x(3+b)=28 | | 2e-6=0 | | 293X-1= | | 1/3x5/6x9/10 | | X-5=9+X | | 7g-11=24 | | (5.4/x)=(.5^6) | | 12+15y-y=12 | | (k^2)-5k-10=0 | | (k^2)-5k+10=0 | | (k^2)-5k-4=0 | | (k^2)-5k+4=0 | | (2-3i)*(x+yi)=5-i | | 4x=6-1 | | 2x+3x-2x= | | 4(m-2)-8+2m=6(m+5) | | Ax+4y+4x+ay= | | x=1.04*y+6.18 | | 2x+3y+1z=51.4 | | X^3/3=65 | | X/3=65 | | 6(y-5)=4(y+2) | | 5y=10x+2 |

Equations solver categories